2018
DOI: 10.1515/aut-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cotton Fibre Maturity by Using Artificial Neural Network

Abstract: Cotton fibre maturity is the measure of cotton’s secondary cell wall thickness. Both immature and over-mature fibres are undesirable in textile industry due to the various problems caused during different manufacturing processes. The determination of cotton fibre maturity is of vital importance and various methods and techniques have been devised to measure or calculate it. Artificial neural networks have the power to model the complex relationships between the input and output variables. Therefore, a model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Farook et al used ANN for cotton fibre maturity. The results showed low error for ANN 20 . Unal et al used ANN and regression for single jersey knitted fabrics to predict air permeability and bursting strength of knit structures.…”
Section: Introductionmentioning
confidence: 87%
“…Farook et al used ANN for cotton fibre maturity. The results showed low error for ANN 20 . Unal et al used ANN and regression for single jersey knitted fabrics to predict air permeability and bursting strength of knit structures.…”
Section: Introductionmentioning
confidence: 87%
“…They selected various fibre characteristics as an input variables and analyzed fibre maturity as an output variable. The simulation results showed that ANN predicted cotton fibre maturity with small error 18 . In another study, Farooq et al proposed ANN to predict the change of shade of dyed knitted fabrics that would happen after finishing application.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, many researcher worked with the prediction of fibre maturity. Farook et al proposed that ANN algorithms are excellent prediction tools in order to predict cotton fibre maturity [ 23 ]. They selected various fibre characteristics as an input variables and analysed fibre maturity as an output variable.…”
Section: Classification Based On Textile Processesmentioning
confidence: 99%